Behavioral Intention Analysis on Aspiring Geopark Tourists: A Case Study in Pangandaran - Hidayah, Riski Taufik; Iskamto, Dedi; Utami, Eristy Minda (International Journal of Entrepreneurship and Business Management, 2023)
Purpose –Pangandaran is still the prima donna of beach tourism in West Java and a favorite tourist destination for domestic tourists so that the Pangandaran area becomes one of the leading tourist areas that has the potential to become a Global Geopark area. This condition is in line with Pangandaran's strength as a mainstay natural tourist destination in West Java which displays aspects of its geodiversity through unique and distinctive rock formations and natural phenomena. Geopark status owned by an area is expected to be able to increase the number of tourist visits that contribute to local economic development. However, there is an imbalance in the visits of domestic tourists and foreign tourists to the Pangandaran tourist area. Methodology/approaches –The method used in this study is verification with the population, namely tourists who have visited the Pangandaran Tourism Area throughout 2021 at least once. The analytical method used is Spearman's rank correlation, the coefficient of determination, and the t test with a significance level of five percent. Findings –This study supports previous studies where the destination image has an influence on the behavioral intention of tourists with a magnitude of 62.09%.